Viewpoint - Understanding Mg corrosion in the body for biodegradable medical implants. (September 2018) - Atrens, Andrej; Johnston, Sean; Shi, Zhiming; Dargusch, Matthew S.
Abstract: Accurate prediction of Mg corrosion rates within the body ( in vivo ) based on laboratory tests ( in vitro ) is a key challenge for Mg alloys in medical applications. Estimates based on in vitro measurements overestimate the measured Mg corrosion rate in vivo . This indicates that the medical environment and the biocorrosion mechanism is not fully characterised. We summarise (i) the relevant Mg metallurgy, and (ii) the solution factors that influence Mg corrosion in vitro . We analyse the reasons for the disparity between the corrosion rates in vivo and the expected corrosion rates based on in vitro testing, and suggest promising areas of research. Graphical abstract: Our best evaluations of the Mg corrosion rate in vivo (MEMp) are significantly larger than the actual measured rates in vivo . Reproduced with permission from Walker et al. [61 ]. Unlabelled Image